2019
DOI: 10.1016/j.jtho.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Versus Docetaxel in a Predominantly Chinese Patient Population With Previously Treated Advanced NSCLC: CheckMate 078 Randomized Phase III Clinical Trial

Abstract: Introduction: Data on immuno-oncology agents in Chinese patients are limited despite a need for new therapies. We evaluated the efficacy and safety of nivolumab in a predominantly Chinese patient population with previously treated NSCLC. Methods: CheckMate 078 was a randomized, open-label, phase III clinical trial in patients from China, Russia, and Singapore with squamous or nonsquamous NSCLC that had progressed during/after platinum-based doublet chemotherapy (ClinicalTrials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
282
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 282 publications
(296 citation statements)
references
References 23 publications
13
282
1
Order By: Relevance
“…A total of 3,691 related studies were identified by the initial search strategy ( Figure S1). Finally, 20 randomized controlled trails with 22 studies involving 12,025 patients were included for the quantitative analysis (Barlesi et al, 2018;Borghaei et al, 2015;Borghaei et al, 2018;Brahmer et al, 2015;Carbone et al, 2017;Fehrenbacher et al, 2016;Gandhi et al, 2018;Govindan et al, 2017;Hellmann et al, 2018;Herbst et al, 2016;Jotte et al, 2018;Langer et al, 2016;Lynch et al, 2012;Mok et al, 2019;Papadimitrakopoulou et al, 2018;Paz-Ares et al, 2018;Reck et al, 2016;Rittmeyer et al, 2017;Socinski et al, 2018;West et al, 2019;Wu et al, 2019). Half of these 22 studies investigated the efficacy of ICI monotherapy versus chemotherapy, including 1 study about avelumab, 2 about ATE, 4 about NIV, and 4 about PEM.…”
Section: Literature Searchmentioning
confidence: 99%
“…A total of 3,691 related studies were identified by the initial search strategy ( Figure S1). Finally, 20 randomized controlled trails with 22 studies involving 12,025 patients were included for the quantitative analysis (Barlesi et al, 2018;Borghaei et al, 2015;Borghaei et al, 2018;Brahmer et al, 2015;Carbone et al, 2017;Fehrenbacher et al, 2016;Gandhi et al, 2018;Govindan et al, 2017;Hellmann et al, 2018;Herbst et al, 2016;Jotte et al, 2018;Langer et al, 2016;Lynch et al, 2012;Mok et al, 2019;Papadimitrakopoulou et al, 2018;Paz-Ares et al, 2018;Reck et al, 2016;Rittmeyer et al, 2017;Socinski et al, 2018;West et al, 2019;Wu et al, 2019). Half of these 22 studies investigated the efficacy of ICI monotherapy versus chemotherapy, including 1 study about avelumab, 2 about ATE, 4 about NIV, and 4 about PEM.…”
Section: Literature Searchmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) targeting programmed cell death-1 (PD-1) or programmed cell death-ligand 1 (PD-L1) play an important role in the treatment of advanced non-small cell lung cancer (NSCLC) without targeted gene mutations, 2,3 which can significantly prolong the overall survival (OS) of patients with advanced NSCLC compared with traditional chemotherapy. [4][5][6][7][8][9][10][11][12][13][14][15][16] At present, nivolumab, pembrolizumab, atezolizumab, and durvalumab have been approved by the United States Food and Drug Administration for the treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…However, most participants in clinical trials of immune‐checkpoint inhibitors have come from western countries, with Asian/East Asian patients accounting for only 3%–25.2% of the study populations in clinical trials of PD‐1/PD‐L1 inhibitors for NSCLC . Few studies have thus reported on the efficacy of immunotherapy and the related characteristics in Asian patients …”
Section: Introductionmentioning
confidence: 99%
“…6.9 months) . The CheckMate 078 trial enrolled predominantly Chinese patients with NSCLC and showed similar efficacy of nivolumab to the CheckMate 017/057 . However, no studies have yet provided direct comparative data regarding the differences in characteristics and prognoses between Asian and white patients with NSCLC, and the relationship between racial differences and the efficacy of immunotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation